Women’s rights in the practice of polygamy in Malaysia / Noordura Mohamed Din, Muhammad Ayman Zaharin and Suhaili Sapun. - Mohamed Din, Noordura; Zaharin, Muhammad Ayman; Sapun, Suhaili (2006)
Our main research deals with how Polygamy is affecting Muslim women in a multicultural society in Malaysia. We do our research by focusing on the Muslim Family Law, a law that only applies to Muslims. We will look at the complexities of implementing a law based on the Qur 'an in a modern multicultural society. Dealing with the complexities means touching upon or going into detail about subjects such as human rights, modernisation, patriarchy and identity. The aim is to understand the contemporary debate about the Polygamy by interviewing people in the debate and ask them to think about, what are the problems? What causes these problems? And how can we solve them? We are focusing on the law because it is a way to understand how women are affected in a basic and practical way. With polygamy our aim is not only to study the impact of the law and the problems women in polygamous marriages are faced with, but the whole idea of forbidding or allowing polygamy in Malaysia. The debate about the Muslim family law will be put into a bigger theoretical framework. This means analyzing the debate and our interviews in a discussion between universal and relativistic values, between a modern interpretation and a traditional interpretation of Islam. Most of all, we want to show how the Muslim family law is affecting women.